Rapid plant identification using species- and group-specific primers targeting chloroplast DNA. - Corinna Wallinger (Public Library of Science (PLoS), 2012)
Plant identification is challenging when no morphologically assignable parts are available. There is a lack of broadly applicable methods for identifying plants in this situation, for example when roots grow in mixture and for decayed or semi-digested plant material. These difficulties have also impeded the progress made in ecological disciplines such as soil- and trophic ecology. Here, a PCR-based approach is presented which allows identifying a variety of plant taxa commonly occurring in Central European agricultural land. Based on the trnT-F cpDNA region, PCR assays were developed to identify two plant families (Poaceae and Apiaceae), the genera Trifolium and Plantago, and nine plant species: Achillea millefolium, Fagopyrum esculentum, Lolium perenne, Lupinus angustifolius, Phaseolus coccineus, Sinapis alba, Taraxacum officinale, Triticum aestivum, and Zea mays. These assays allowed identification of plants based on size-specific amplicons ranging from 116 bp to 381 bp. Their specificity and sensitivity was consistently high, enabling the detection of small amounts of plant DNA, for example, in decaying plant material and in the intestine or faeces of herbivores. To increase the efficacy of identifying plant species from large number of samples, specific primers were combined in multiplex PCRs, allowing screening for multiple species within a single reaction. The molecular assays outlined here will be applicable manifold, such as for root- and leaf litter identification, botanical trace evidence, and the analysis of herbivory.